Pearls of Wisdom: A Perioperative Work Environment Based on Values - Shewchuk, Muriel (Operating Room Nurses Association of Canada Journal, 2003)
The current perioperative work environment is often frustrated with many negative, daily occurrences. It is not uncommon to hear complaints of " they just don’t seem to care like they used to"; "late yet again"; "sick again — nothing wrong with her yesterday — oh by the way its Monday or Friday, what do you expect- I could have written the sick list names in advance"; “ she never prepares for the surgery — doesn't know the anatomy, has not pre—read the pick list, isn't organized, table is a mess, count is mixed up, is not keeping up with the surgeon never mind anticipating with pride and efficiency" and the interminable "stays too long at breaks". This list can go on and on, you have heard it all and uttered the same words. What can we do to turn it around, how do we change the environment to one of - "Yeh, lets get to work!"